2011
DOI: 10.1002/path.2836
|View full text |Cite
|
Sign up to set email alerts
|

Effects of targeting the VEGF and PDGF pathways in diffuse orthotopic glioma models

Abstract: Currently available compounds that interfere with VEGF-A signalling effectively inhibit angiogenesis in gliomas, but influence diffuse infiltrative growth to a much lesser extent. Development of a functional tumour vascular bed not only involves VEGF-A but also requires platelet-derived growth factor receptor-β (PDGFRβ), which induces maturation of tumour blood vessels. Therefore, we tested whether combined inhibition of VEGFR and PDGFRβ increases therapeutic benefit in the orthotopic glioma xenograft models E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 66 publications
8
33
1
Order By: Relevance
“…The differences in VEGF expression of the tumors in distinct locations originating from the same cell line confirm that the orthotopic microenvironment and the resulting growth pattern significantly influence gene expression in glioma cells, a phenomenon that has been described previously (19,20). Moreover, it has been shown that in glioblastoma, VEGF is predominantly overexpressed in hypoxic, perinecrotic cells (35,36). Indeed, in our study, the VEGF expression in subcutaneous E98FM tumors was especially present around areas of necrosis, whereas in intracranial E98FM tumors, necrosis and VEGF expression were lacking and this also coincided with lack of bevacizumab uptake studied ex vivo and by PET.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The differences in VEGF expression of the tumors in distinct locations originating from the same cell line confirm that the orthotopic microenvironment and the resulting growth pattern significantly influence gene expression in glioma cells, a phenomenon that has been described previously (19,20). Moreover, it has been shown that in glioblastoma, VEGF is predominantly overexpressed in hypoxic, perinecrotic cells (35,36). Indeed, in our study, the VEGF expression in subcutaneous E98FM tumors was especially present around areas of necrosis, whereas in intracranial E98FM tumors, necrosis and VEGF expression were lacking and this also coincided with lack of bevacizumab uptake studied ex vivo and by PET.…”
Section: Discussionsupporting
confidence: 62%
“…Also in DIPG, decreased phosphoVEGR2 levels in peripheral blood mononuclear cells (PBMC) did not correlate with treatment response (15). In the E98 xenograft model used in this study, treatment with bevacizumab did not increase survival, nor did it influence the growth pattern in the diffusely growing parts of the tumor (36). This suggest simply decreasing VEGF in the blood pool is, at least for the tumor types studied and our xenograft model, often insufficient for adequate tumor targeting and instead, local bevacizumab accumulation seems needed (47)(48)(49).…”
Section: Discussionmentioning
confidence: 68%
“…Athymic female BALB/c nu/nu mice (18–25 gram, age 6–8 weeks) were kept under specified pathogen-free conditions and received food and water ad libitum . E98 and E434 cells were grown as spheroids in supplemented neurobasal medium for at least two weeks prior to orthotopic injection [29]. A 20 μL cell suspension (10 7 cells/mL in PBS) containing a mixture of shSCR/GFP and shPTPRZ1/TagRFP labeled cells was injected per animal (n=5 and 4 for E98 and E434 cells, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Various methods are used clinically to assess antiangiogenic therapies in tumors; these methods include measuring blood flow and blood volume (dynamic contrast-enhanced CT and MR imaging), which assess the downstream effects of angiogenesis (24)(25)(26). However, PET imaging has the ability to directly measure processes in the angiogenesis pathway and potentially provide a more specific means to assess antiangiogenic therapy efficacy in tumors.…”
Section: Discussionmentioning
confidence: 99%